FRI0086 CHINA-MANUFACTURED ADALIMUMAB BIOSIMILAR, HLX03, DEMONSTRATED PHARMACOKINETIC EQUIVALENCE AND COMPARABLE SAFETY TO REFERENCE ADALIMUMAB. (June 2019) - Sun, Jixun; Chen, Guiling; Wu, Min; Han, Yiwen; Gao, He; Zhang, Tianli; Guo, Xinjun; Zhang, Xin; Liu, Eugene; Luk, Alvin; Jiang, Weidong; Liu, Scott; et al.
Abstract : Background: Adalimumab first launched in China in August 2010 with now more than 10 million people have its indications. 1, 2 However, the relative high cost of the biologic drug limits the treatment accessibility and reduces the quality of life in patients living with the chronic inflammatory disease like rheumatoid arthritis and psoriasis. In accordance with the China National Medical Product Administration (NMPA) biosimilar regulatory development pathway, biosimilar products require to demonstrate similarity in pharmacokinetics (PK) and safety profile compared to its reference drug, which could further address the unmet medical needs of adalimumab. HLX03 was developed as a proposed biosimilar to adalimumab with the potential to increase affordable treatment options for access. Objectives: The study was aiming to compare the pharmacokinetics (PK), safety and immunogenicity of the proposed adalimumab biosimilar HLX03 with reference product. Methods: We conducted a randomised, double-blind, parallel-controlled clinical trial (NCT03357939 ) in China to compare the PK, safety and immunogenicity of HLX03 and China sourced adalimumab (CN-adalimumab). In this study, 211 healthy volunteers were randomised 1:1 to receive a single (40 mg) subcutaneous injection of HLX03 or CN-adalimumab. The primary PK endpoints were area under the curve (AUC) from time zero to the last quantifiable concentration (AUC0-t ) and maximum observed concentration (Cmax ), secondary endpoint was AUC from time zero to infinity (AUC0-inf ). PK equivalence was established if the 90% confidence interval (CI) for the test-to-reference ratio fall within the 80-125% equivalence margin. Results: Based on the analysis of 210 subjects in the per protocol population (PPS) and 211 subjects in the full analysis set (FAS), HLX03 demonstrated PK equivalence to CN-adalimumab for all primary endpoints (Table 1). The incidents of adverse events (AEs) between two treatment groups were similar, with treatment-emergent AEs (TEAEs) noted by a total of 149 (70.0%), 79 (73.8%) in HLX03 and 70 (66.0%) in CN-adalimumab group, respectively. One subject suffered non-drug-related severe AE (tuberculosis) in the HLX03 arm, and one subject occurred grade 4 AE (elevated creatine phosphokinase) in the CN-adalimumab arm. In the group of CN-adalimumab, 6 more incidents of positive anti-drug antibodies (ADA) recorded at day 7 and no further significant difference observed. Based on the established clinical PK equivalence and safety similarities, 262 patients with moderate-to-severe chronic plaque psoriasis were randomized in 21 centers at 1:1 ratio to conduct a double-blind, parallel-controlled phase 3 study (NCT03316781 ) to further evaluate the efficacy and safety profiles of HLX03 and reference adalimumab. The primary efficacy endpoint was the improvement rate of Psoriasis Area and Severity Index (PASI) over the baseline at week 16. Conclusion: PK equivalence and safety similarities between HLX03 and CN-adalimumab were demonstrated which leads to a multi-center, randomised, double-blind, parallel-controlled phase 3 study to further evaluate the efficacy and safety of HLX03 as the proposed biosimilar of adalimumab in patients with moderate-to-severe plaque psoriasis. References: [1] Chinese Rheumatology Association. 2018 Chinese guideline for the diagnosis and treatment of rheumatoid arthritis[J]. Zhonghua nei ke za zhi, 2018, 57(4): 242. [2] Markets, R. (2018). Investigation Report on China Adalimumab Market, 2010-2018. Retrieved from https://www.prnewswire.com/news-releases/investigation-report-on-china-adalimumab-market-2010-2018-252895801.html Disclosure of Interests: Jixun Sun Grant/research support from: research funding, Guiling Chen Grant/research support from: research funding, Min Wu Grant/research support from: research funding, Yiwen Han Employee of: I am an employee of Shanghai Henlius Biotech, Inc., He Gao Employee of: I am an employee of Shanghai Henlius Biotech, Inc., Tianli Zhang Employee of: employee of Shanghai Henlius Biotech, Inc., Xinjun Guo Employee of: Employee of Shanghai Henlius Biotech Inc., Xin Zhang Employee of: I am an employee of Shanghai Henlius Biotech, Inc., Eugene Liu Employee of: I am an employee of Shanghai Henlius Biotech, Inc., Alvin Luk Employee of: I am an employee of Shanghai Henlius Biotech, Inc., Weidong Jiang Shareholder of: I am the co-founder of Shanghai Henlius Biotech, Inc., Employee of: I am an employee of Shanghai Henlius Biotech, Inc., Scott Liu Shareholder of: I am the CEO of Shanghai Henlius Biotech, Inc., Employee of: I am an employee of Shanghai Henlius Biotech, Inc., Katherine Chai Employee of: I am an employee of Shanghai Henlius, Yanhua Ding Grant/research support from: research funding